Composting for a More Sustainable Palm Oil Waste Management: A Systematic Literature Review - Jajang Supriatna; Mieke Rochimi Setiawati; Rija Sudirja; Cucu Suherman; Xavier Bonneau (The Scientific World Journal)
Palm oil production has increased significantly, specifically in Indonesia and Malaysia. However, this growth has raised environmental concerns due to the high discharge of empty fruit bunches, palm oil mill effluents, and other solid wastes. Therefore, this study aims to examine the treatment of palm oil waste by composting and systematically review insights into its application through a systematic literature review approach. Among the 1155 articles, a total of 135 were selected for a systematic review of palm oil waste management developments and their applications, while 14 were used for determining compost quality according to the criteria and requirements established in the systematic literature review. Moreover, using Egger’s test, JAMOVI 1.6.23 software was used to analyze random effects models with 95% confidence intervals and publication bias. The results showed that palm oil waste was optimally treated by composting, which is considered as a sustainable technology for protecting the environment, human safety, and economic value. The in-vessel method with a controlled composting chamber is the best system with a minimum time of 14 days. However, it requires tight control and provides a final product with a high microbial colony form outdoors and indoors compared to the windrow system. This study is useful to see the bias of research results and helps to find new studies that need to be developed, especially in this case related to the management of palm oil waste into organic compost fertilizer and its application methods in the field. It is suggested that applying palm oil waste or compost is mainly performed by mulching. In contrast, new challenges for better processing to produce organic fertilizers and applicable technologies for sustainable waste management are recommended. The method must be affordable, efficient, and practical, combining compost quality with maximum nutrient recovery.